(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
Advertising, one of the first and most relevant consumer rhetorics, has been undergoing visceral transformations in its modus operandi, due, among other factors, to the use of algorithms and generative artificial intelligence. The same occurs in terms of its communicational frameworks, responding to social pressure with the inclusion of agendas and representations that were previously silenced. Given this context, how to teach advertising creation? This article reports a methodological experience applied in the classroom in advertising courses and demonstrates that investment in literature not only generates a more attractive form of teaching but also deepens the human dimension in students.